Effect of total flavones of Clematis filamentosa Dunn on the oxLDL-induced injury of vascular smooth muscle cells by regulating miR-455-5p - Xia, Xiaolin; Wang, Junlian; Liu, Qifang (Cellular and Molecular Biology, 2020)
This experiment was conducted to investigate whether total flavones of Clematis filamentosa Dunn affect the inflammatory response and apoptosis of vascular smooth muscle cells induced by oxidized low-density lipoprotein (oxLDL) by regulating microRNA-455-5p (miR-455-5p). 50 mg/mL oxLDL was performed to stimulate the injury of vascular smooth muscle cells, and the total flavones of Clematis filamentosa Dunn were added at concentrations of 75, 150, and 300 Î¼g/mL. The expressions of inflammatory factors IL-1Î² and TNF-Î± were analyzed by ELISA, the apoptosis was evaluated by flow cytometry, the expression of Bcl-2 and Bax was determined by western blot, and the real-time fluorescence quantitative PCR (qRT-PCR) was applied to detect miR-455-5p expression. MiR-455-5p mimic was transfected into vascular smooth muscle cells and then induced injury with oxLDL; miR-455-5p inhibitor was transfected into vascular smooth muscle cells and treated with oxLDL and 300 Î¼g/mL total flavones of Clematis filamentosa Dunn. The above methods were employed to investigate the inflammatory response and apoptosis of cells. The total flavones of Clematis filamentosa Dunn significantly inhibited the expression of IL-1Î², TNF-Î±, apoptosis rate, Bax protein expression of oxLDL induced vascular smooth muscle cells, and remarkably promoted the expression of Bcl-2 protein and miR-455-5p, which all showed concentration dependence (p<0.05). Overexpression of miR-455-5p reduced IL-1Î², TNF-Î± expression, apoptosis rate, Bax protein expression, and greatly increased Bcl-2 protein expression in oxLDL injured vascular smooth muscle cells (p<0.05). After interfering with the expression of miR-455-5p, the inhibitory effect of total flavones of Clematis filamentosa Dunn on the expression of IL-1Î², TNF-Î±, apoptosis, Bax protein expression of oxLDL-induced vascular smooth muscle cells was reversed, and its promotion effect on Bcl-2 protein expression was also reversed. Total flavones of Clematis filamentosa Dunn can reduce oxLDL-induced vascular smooth muscle cell inflammation and inhibit its apoptosis. The mechanism of action is related to the up-regulation of miR-455-5p expression.